“Symmetrical” hermit crabs of the family Pylochelidae (Crustacea: Decapoda: Anomura) collected by the “BIOPAPUA” and “PAPUA NIUGINI” expeditions in the Papua New Guinea, with descriptions of two new species - Komai, Tomoyuki; Chan, Tin-Yam (Zootaxa, 2016)
Collections made during the recent expeditions to Papua New Guinea (“BIOPAPUA”, 2010; “PAPUA NIUGINI”, 2012) yielded a total of 12 species from the “symmetrical” hermit crab family Pylochelidae, including two new to science: Bathycheles incisus (Forest, 1987), B. integer (Forest, 1987), Cheiroplatea laticauda Boas, 1926, C. pumicicola Forest, 1987, C. rotundioculus n. sp., Pylocheles mortensenii Boas, 1926, and Xylocheles macrops (Forest, 1987) (Pylochelinae); Parapylocheles scorpio (Alcock, 1894), Trizocheles manningi Forest, 1987, T. moosai Forest, 1987, T. sakaii Forest, 1987, and T. spinidigitus n. sp. (Trizochelinae). Affinities of the two new species are discussed. Parapylocheles scorpio, Trizocheles manningi and T. sakaii are recorded from the South Pacific for the first time. Revised identification keys to species of Cheiroplatea and Trizocheles are provided.